(untitled) (Research, Society and Development, 2021)
Objective: To understand, based on data in the literature, the factors that are related to the choice of delivery method. Method: This is an integrative literature review prepared according to the steps, proposed by Mendes, Silveira and Galvão. The study covered the years 2015 to 2020 of the Scientific Electronic Library Online (Scielo) and Virtual Health Library ( Bireme). Results: Twelve articles were selected and analyzed, highlighting the factors related to the choice of delivery method. The study revealed that the choice of the mode of delivery is related to cultural and social factors and to an interventionist model, it is also noticed that women who performed their prenatal care in a private network manifest autonomy in choosing the decision. The cesarean, in addition to the convenience of scheduling the child’s delivery, avoids pain and identifies that the decision is concentrated in the power of health professionals. Discussion: In this way, when we reflect on the routes of childbirth, we involve biological, psychological, social, cultural aspects and the experience of pain, the professional nurse has a fundamental role in the informative and educational conduct in prenatal care, solving their doubts, fears, anxieties. Conclusions: The study contributes to the training of professional nurses, training people who understand childbirth as a physiological event, aiming at a service based on the humanization of care that guarantees autonomy, female empowerment, improving the quality of care, especially with regard to guidelines provided to the pregnant woman, which will guide her for her best choice.